An Investigation into the Influence of C. moschata Leaves Extract on Physicochemical and Biological Properties of Biodegradable PCL/PLA Blend Film - Pekdemir, Sibel; Oner, Ecem Ozen; Pekdemir, Mustafa Ersin; Dalkilic, Semih; Dalkilic, Lutfiye Kadioglu (Springer, 2022)
Poly epsilon-caprolactone (PCL) synthesized by ring-opening polymerization method, and then it blended with polylactic acid (PLA). The blend was loaded with Cucurbita moschata leaf extract. The prepared PCL/PLA blend loaded with C. moschata was characterized with ATR-IR, TGA, and DSC; also the surface morphology was examined with an optical microscope. The thermal analysis results showed that the plant extract reduces the thermal stability and melting temperatures of the pure polymer blends. Optical microscope images showed that the plant extract filled the spaces between the polymer molecules. The antimicrobial effects of the pure polymer blend, pure plant leaf extract, and plant-loaded polymer blend against Staphylococcus aureus, Klebsiella pneumoniae, Escherichia coli, Bacillus megaterium, and Candida albicans microorganisms were examined, and it was observed that the antimicrobial effects increase with increasing concentration. Finally, the cytotoxic activities of the samples on the human breast cancer (MDA-MB-231) cell line were performed by the MTT analysis method. While the C. moschata leaf extract and polymer blend showed cytotoxic effect, the cytotoxic effect of the polymer blend loaded with plant extract was quite low.
Keywords: PCL; Cucurbita moschata; Shape memory polymer; Antimicrobial; Cytotoxicity